Metaphysics - Pestana, Mark (IntechOpen, 2012)
It is our hope that this collection will give readers a sense of the type of metaphysical investigations that are now being carried out by thinkers in the Western nations. We also hope that the reader's curiosity will be peaked so that further inquiry will follow.